−3(−13+m)+11: Apply the Distributive Property.
= −3⋅(−13) + −3⋅m + 11
= 39 + −3⋅m + 11
−3⋅m+__+11: Apply the Commutative Property of Addition and add.
= −3⋅m + 39 + 11
= −3⋅m + 50
−3⋅m+50: Apply the Inverse Property of Multiplication.
= −3⋅m + 12
Therefore, −3(−13+m)+11 is equivalent to −3⋅m+12.
Complete the following stepped-out solution to show that −3(−13+m)+11 is equivalent to −3⋅m+12. −3⋅__+(−3⋅m)+11: Apply the Distributive Property. __+(−3⋅m)+11: Apply the Inverse Property of Multiplication. −3⋅m+__+11:Apply the Commutative Property of Addition and add.
1 answer